Influence of temperature variation on the generation of a photovoltaic system connected to the grid for power generation under field conditions (Research, Society and Development, 2021)
This experiment aimed to analyze the temperature behavior of photovoltaic modules, with the efficiency of the on-grid photovoltaic system, installed at the State University of West Paraná - UNIOESTE, campus of Cascavel, Paraná. The photovoltaic system consists of two ropes, with a total power of 3.3 kWp. In the first period, it was found that the panel kept clean (Panel 2), during data collection, reached a higher efficiency during the first weeks and practically the same for the last weeks, compared to the dirty panel. Achieve an average efficiency of 13.73% and 14.39%, Panel 1 and Panel 2, respectively. For the second period, the average efficiency of both panels, with inclinations of 21° and 26°, was very close, being 14.25% (Panel 1) and 14.24% (Panel 2). The third period showed a difference in the efficiency of the panels, 13.7% (Panel 1) and 14.54% (Panel 2), with inclinations of 21° and 18°, respectively. The test of means identified that there was a difference between the levels of soiling of the modules, as well as their inclinations of 21° and 18°. As for the 21° and 26° inclinations, there was no significant difference, according to the Tukey Test at 5% significance.